Comparing the performance of three panels rules of blood smear review criteria on an Italian multicenter evaluation. (3rd October 2017) - Pipitone, S.; Germagnoli, L.; Da Rin, G.; Di Fabio, A.; Fanelli, A.; Fiorini, F.; Francione, S.; Marini, A.; Papa, A.; Benegiamo, A.; Lari, T.; Siviero, F.; et al.
Abstract: Background: The aims of this study were to compare the diagnostic accuracy of blood smear review criteria, by means of three different panel rules, those proposed by: the International Consensus Group for Hematology [41‐ICGH rules], the Italian Survey [IS rules] and the Working Group on Hematology‐SIBioC (WGH) consensus rules (WGH rules). Methods: This study is based on 2707 peripheral blood (PB) samples referred for routine hematological testing to the WGH‐associated laboratories displaced all over the Italian territory. The PB samples were processed on seven different hematology analyzers (HAs): Advia 2120i, XE‐2100, BC‐6800, ABX Pentra, XN‐1000, Cell‐DYN Sapphire, and DxH800, respectively. All the results provided by the HAs were analyzed through the application of three different blood smear review criteria: that is, the 41‐ICGH, IS, and WGH rules. Finally, data were compared with those obtained by optical microscopy (OM), as the current gold standard. Results: The overall the agreement OM classification with ICGH, IS, and WGH panel rules is 0.83, 0.83, and 0.85, respectively. The false negatives are 2.1%, 3.0%, and 2.9%, while false positives are 15.1%, 13.7%, and 11.7%, respectively. All the seven HAs showed variable interinstrument performance, as three different criteria for OM review were adopted on each of them from time to time. Conclusion: These results presented show that the customization of validation rules is necessary for enhancing the quality of hematological testing and optimizing workflow.